Occupational Irritan Contact Dermatitis Among Shipyard Workers in Samarinda, Indonesia (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Occupational irritant contact dermatitis (OICD) is still a occupational health problem. Shipyard workers are susceptible to OICD. A cross sectional study was conducted on 32 samples of shipyard workers in Samarinda to analyze the prevalence of OICD and related factors. The dependent variable is OICD, while independent variable consists of age, length of service, length of contact, history of skin diseases, personal hygene and personal protective equipment. Data collection through interview and direct observation, data analysis using Phi test and multiple logistic regression. All respondents had OICD and significantly correlated with working period (p = 0.001), history of skin disease (p = 0.004), personal hygene (p = 0.003) and use of PPE (p = 0.05). History of skin disease (B = 1.116) and use of PPE (B = 1.053) are most dominant variables. Personal hygiene improvements, tightening monitoring of use of PPE and improving occupational health efforts have been suggested.